Patient Satisfaction on Services Rendered by Malasakit Center in Amang Rodriguez Memorial Medical Center - Habon, Mary Apple F.; Jamandre, Ma. Venessa B.; Malco, RRexy T.; Vigonte, Florinda G.; Malang, Bernandino P.; Abante, Marmelo V. (Future Science / FSH-PH Publications, 2023)
This study was carried out to determine the level of patient satisfaction with the services rendered by the Malasakit Center in Amang Rodriguez Memorial Medical Center. It aimed to identify the service frequently requested by the patient and/or their representative and its frequency, as well as the level of satisfaction. This study employed descriptive research to describe the nature of the situation that existed in the study together with a survey questionnaire as the research instrument tool. The 125 respondents were selected through convenience sampling. The findings of this study revealed that most of the patients and their representatives’ access Malasakit centers with the query on the document requirement. Eight other services were also sought from the Malasakit Center such as medical help/aid, follow up and status of the documents submitted. These services were rated with a high level of satisfaction with a weighted mean rating of 3.84. The study concluded that various services were accessed by the patients and/or patients' representatives. The patients' and/or patients' representatives' degree of satisfaction with the service of the Malasakit Center at the Amang Rodriguez Memorial Medical Center is extremely high or highly satisfactory. The health practitioners will be educated and equipped to handle the services provided by the Malasakit Center as a result of these measures.